The Effect of Convenience and Trust on Online Purchasing Decision (on Blibli Platform) - Wahyu Abdurrahman Rasidi Rasidi; Monika Tiarawati (Profesional Muda Cendekia Publishing, 2021)
The rapid development of business is supported by advancement in information technology media so that electronic commerce (e-commerce) comes to the ground such as Tokopedia, Bukalapak, Blibli, Lazada Shopee and JD.ID. This study analyzed and discussed the effect of convenience and trust on online purchasing decision on Blibli platform. The data processing in this study was done by using multiple linear regression with non-probabilty sampling technique used was judgmental sampling on a sample of 100 respondents. The results of this study indicated that convenience did not have significant effect on purchasing decision on Blibli website and trust has a significant and positive effect on purchasing decision on Blibli website.